Ιδεολογικές συνέπειες της κοινωνικής διαμάχης στη Σμύρνη: (1809-1810) - Κιτρομηλίδης, Πασχάλης Μ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1982)
One of the most articulate sources of social criticism of the Neohellenic Enlightenment has been preserved in an Athonite manuscript and although known to earlier researchers it has remained unpublished apparently because of its radical anticlerical bent. The original stimulation for the composition of the text was provided by the conservative reactions which managed to temporarily close down the school of modern learning (Philological Gymnasium) in Smyrna after its first year of operation (1809 - 1810). The anonymous author gives many details about the social conflicts in the city, talks about the persecution of the Enlightened intelligentsia in Western Asia Minor by conservative clerical intellectuals and broadens his attack against the exploitative social practices and corruption that characterized the conduct of most hierarchs of the Orthodox Church in the period just before the outbreak of the Greek Revolution. This is a first attempt to make large sections of this important source available to the study of Modern Greek thought. Those parts of the text that present special theoretical or historical interest are edited and published, followed by the detailed commentary and documentation which is necessary to place the text in its relevant context.